Internationalization and portuguese as a foreign language (PFL): survey and discussion - Guimarães, Felipe Furtado; Finardi, Kyria Rebeca (Universidade Estadual de Campinas, 2021)
This study aimed at developing a survey about the courses of Portuguese as a Foreign Language (PFL) in Brazilian higher education institutions (HEIs), and discussing the delivery of these courses in relation to the process of internationalization. Therefore, data from 60 Brazilian HEIs were collected through an online questionnaire, in order to support the discussion about the relationship between PFL and internationalization, based on the literature and data collected. Results indicate that most institutions offer PFL courses, the Southern region being significant for the PFL offer, and the departments of Languages and international relations (taken together) are responsible for great part of this offer. The discussion of results suggests a relevant connection between PFL and Internationalization at Home (IaH). Conclusions indicate that, despite the efforts of HEIs to offer PFL, more investment is necessary to develop IaH, in order to promote social justice.